S0 Lamb Wave Scattering from a Cylindrical Inhomogeneity in a Transversely Isotropic Composite Plate - 张海燕 姚杰聪 王瑞 马世伟 (Chinese physics letters, 2014)
An analytical model using the Poisson theory is proposed to predict the SO Lamb wave scattering from a cylindrical inhomogeneity in a transversely isotropic composite plate. Due to the anisotropic elastic properties of the plate, the suitability of the model is first examined by the dispersion curve of an SO wave by using approximate Poisson theory compared to the exact Lamb solution. It is found that the Poisson theory can accurately describe the behavior of the SO wave at low frequency when the incident SO wave is parallel or perpendicular to the fiber direction of the transversely isotropic composite plate. On this basis, making use of the wave function expansion technique and coupling conditions at the inhomogeneity defect boundary, the far field scattered patterns of various inhomogeneity sizes and properties are then explored. The present results reveal that the scattering patterns are strongly dependent on the size and stiffness of the cylindrical inhomogeneity.